Pemanfaatan Limbah Ampas Tebu Menjadi Briket Bio-Batubara Menggunakan Perekat Tapioka - Prayoga, M. Ilham Dio; Tamrin, Tamrin (abe.fp.unila.ac.id, 2023)
The research carried out aims to utilize bagasse waste and determine the characteristics of bio-coal briquettes made from bagasse waste with the addition of coal. This research was conducted with reference to a completely randomized design (CRD) with two factors and three replications. The first factor is the comparison of the composition of the main raw materials in the form of bagasse and coal (P) which includes four treatment levels, namely 100%: 0% (P0), 40%: 60% (P1), 60%: 40% (P2) and 80 %: 20% (P3).The second factor is the concentration ratio of tapioca adhesive which includes three treatment levels, namely 10% (K1), 15% (K2) and 20% (K3). There are seven parameters tested in this study, namely density, moisture content, compressive strength, shatter resistance index, calorific value, combustion rate and basic temperature of the cooking pancie when burning briquettes.The results showed that the higher the percentage of coal in the composition of the main raw material tends to increase the compressive strength and decrease the burning rate of the briquettes. Meanwhile, the lower the tapioca adhesive concentration used tends to increase the density, compressive strength, and shatter resistance index and reduce the burning rate of briquettes. The briquettes produced in this study resulted in the following characteristics: briquette density ranged from 0.36 to 0.44 g / cm3, the moisture content ranges from 4.04% - 6.42%, compressive strength ranges from 26.87 - 46.15 N / cm2, the shatter resistance index ranges from 96.02% - 96.78%, the actual heating value ranges from 3266.1 - 4588.5 cal / g, the theoretical calorific value ranged from 1988.1 to 4483.6 cal / g, the briquette combustion rate ranged from 1.818 to 3.125 g / min, and the highest basic cooking pancie temperature was obtained in the P1K1 treatment combination of 229ºC. Keywords: Briquettes, Coal, Tapioca Glue, Waste Bagasse.